2018
DOI: 10.3174/ajnr.a5692
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Susceptibility Mapping after Sports-Related Concussion

Abstract: Background and Purpose Quantitative Susceptibility Mapping (QSM) using MRI can assess changes in brain tissue structure and composition. This report presents preliminary results demonstrating changes in tissue magnetic susceptibility after sport-related concussion (SRC). Materials and Methods Longitudinal QSM metrics were produced from imaging data acquired on cohort of concussed and control football athletes. 136 QSM datasets were analyzed across three separate visits (24 hours after injury, 8 days post-inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
3
27
1
Order By: Relevance
“…Yet there has been a lag in the acceptance of the method for the analysis of traumatic axonal injury. Recently, Koch et al reported increased QSM values in concussion patients in white and gray matter within 24 h post-injury that persisted up to 8 days and normalized after 6 months (44). Pathophysiological reasons for the changes were not provided.…”
Section: Introductionmentioning
confidence: 99%
“…Yet there has been a lag in the acceptance of the method for the analysis of traumatic axonal injury. Recently, Koch et al reported increased QSM values in concussion patients in white and gray matter within 24 h post-injury that persisted up to 8 days and normalized after 6 months (44). Pathophysiological reasons for the changes were not provided.…”
Section: Introductionmentioning
confidence: 99%
“…QSM images were reconstructed from Siemen’s magnitude and phase images using nonlinear dipole inversion [ 23 ] and MATLAB. To investigate for brain-wide changes in gray matter and white matter susceptibility we generated global gray and white matter masks based on an automated method that incorporates a stability mask [ 11 , 12 ]. Global grey and white matter masks were generated by first excluding voxels with R 2 * less than 1 ms −1 and greater than 65 ms −1 to remove large vessels such as the straight sinus from the final gray matter mask.…”
Section: Methodsmentioning
confidence: 99%
“…A stability mask was then constructed by computing coefficients of variability with an upper threshold of 0.8. White and gray matter were subsequently defined as χ < − 0.03 ppm and χ > 0.05 ppm, respectively and mean susceptibility values were then calculated for each [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments used a GE Healthcare Discovery MR750 3.0T system (GE Healthcare, Waukesha WI) with a 32‐channel head receive coil (Nova Medical, Wilmington MA). Data from five participants enrolled in a larger study of sport concussion 34 were preserved for off‐line reconstruction. Imaging parameters included: 30 ms TE, 800 ms TR, 503 repetitions, a 50° flip angle, 104 × 104 acquisition matrix, 63% partial Fourier encoding, 20.8 cm sagittal field of view, 2 mm thick slices, 8‐band simultaneous multi‐slice acceleration, 13 blipped‐CAIPI field of view shift, and 64 total slices, harmonized with the Lifespan Human Connectome Project acquisition protocol 35 .…”
Section: Methodsmentioning
confidence: 99%